Synergistic activation of CO2 and H2 by Ru-Oxygen vacancy pairs over porous CeO2 for efficient formic acid synthesis - Liujun Wang; Shufeng Lin; Junfeng Qian; Yingjun Wang; Zhe Wang; Zhonghua Sun; Zhihui Zhang; Bing Lu; Mingyang He; Zhenzhen Wang (Fuel, 2026)

Genomic insights into high GABA production by Levilactobacillus brevis Q3–11 and its application in developing functional kiwifruit juice - Bingrui Guo; Qi Wu; Xu Yan; Wei Ji; Shufeng Yin; Sufang Zhang; Yiwei Dai; Xiangyu Sun; Tingting Ma; Xinping Lin (International Journal of Food Microbiology, 2026)

Improving the quality and safety of fermented mandarin fish (Siniperca chuatsi) by co-inoculation with Latilactobacillus sakei A20 and Lactiplantibacillus plantarum LJ1–1 - Shufeng Yin; Bingrui Guo; Wenqing Wang; Wei Ji; Siqi Zhang; Changlei Ji; Chaofan Ji; Yiwei Dai; Sufang Zhang; Xinping Lin (Food Research International, 2026)

Moderate fermentation contributes to favorable flavor and quality: Insights from full-length 16S rRNA sequencing analysis of different brands of Chouguiyu - Hao Liu; Xu Yan; Ying Yue; Shufeng Yin; Ning Zhao; Chaofan Ji; Yingxi Chen; Sufang Zhang; Yiwei Dai; Xinping Lin (Food Bioscience, 2026)

Continuous-flow CO2 hydrogenation to formic acid over Pd-based catalysts on amine-functionalized Zr-SBA-15 - Zhenzhen Wang; Shufeng Lin; Liujun Wang; Zhe Wang; Bing Lu; Zhonghua Sun; Zhihui Zhang; Mingyang He; Junfeng Qian (Fuel, 2026)

Lactiplantibacillus pentosus JWN01 and Lactiplantibacillus plantarum JWN02 attenuate renal fibrosis and pathological autophagy in hyperuricemic nephropathy via gut–kidney axis - Qizhou Mo; Min Qin; Haiqi Liang; Liwei Wei; Yujian Li; Yangmei Qin; Lichun Tang; Jing Liang; Chong Qian; Yilong Liang; Shufeng Luo; Yutuo Wei; et al. (Food Research International, 2026)

Cenozoic out-of-sequence structural expansion across the northern Tibetan Plateau margin: Insights from differential exhumation of the Altyn Shan and basin deformation - Shibao Gao; Xiaogan Cheng; Xiubin Lin; Baotian Pan; Yuhui Ye; Lei Wu; Kaixuan An; Hanlin Chen; Shufeng Yang (Tectonophysics, 2025)

Latitudinal Beta‐Diversity Gradient of Riverine Macroinvertebrate: Interplays of Climatic and Land Use Factors - Ruxia Qiao; Hanrui Wang; Yuqing Lin; Qiuwen Chen; Jianyun Zhang; Kai Chen; Tao Feng; Shufeng He; Hanlu Yan (Global Ecology and Biogeography, 2025)
Aim Climate change and land use have major effects on macroinvertebrate biodiversity, but it is unclear how they shape spatial variations, particularly at large scales. This study explored the latitudinal patterns of beta diversity in riverine macroinvertebrate assemblages and examined how they are shaped by climate and land use. Location China (18°–48° N). Time Period From 2006 and 2021. Major Taxa Studied Riverine macroinvertebrates. Method A comprehensive dataset covering macroinvertebrate taxa from 42 watersheds across China was compiled to explore the latitudinal patterns of taxonomic, functional, and phylogenetic beta diversities, including turnover and nestedness components. Generalised additive models were used to assess the impacts of climatic and land use variables, selected from 20 climatic and 10 land use candidates, on latitudinal patterns of beta diversity. Results Taxonomic and functional beta diversities shared a non‐monotonic latitudinal pattern, minimised at 24°–30° N, contrasting with the monotonic increase in phylogenetic beta diversity. Taxonomic beta diversity was dichotomously regulated by climatic stability and land use: diminishing nestedness in low‐latitude regions while augmenting spatial turnover in high‐latitude regions as latitude increased. For functional beta diversity, climate was identified as an indirect factor influencing historical trait‐pool constraints, whereas land use was identified as a direct factor altering its nestedness component. Phylogenetic beta diversity demonstrated no significant association with contemporary environmental variables. Main Conclusions This study uncovers three facets of macroinvertebrate beta diversity with different latitudinal patterns, highlighting the disparate influences played by climate and land use on these spatial differences as well as the distinct importance of processes causing nestedness and turnover. These insights provide a foundation for latitude‐specific conservation strategies that aim at preserving the macroinvertebrate diversity in rivers.

Limited intracontinental convergence accommodated by lithospheric-scale wedge tectonics along the northeastern margin of the Tibetan Plateau - Kun Li; Lei Wu; Bo Guo; Guoli Liu; Xiubin Lin; Ancheng Xiao; Shufeng Yang; Hanlin Chen (Science China Earth Sciences, 2025)

Salinity as a key factor affects viral structure, function, and life strategies in lakes from arid and semi-arid regions - Haojun Lei; Nuowen Zhou; Jinhong Zhang; Ruifeng Lin; Tianyi Chen; Jiang Wu; Lei Su; Shufeng Liu; Tang Liu (Journal of Hazardous Materials, 2025)

Flavour enhancement of dry fermented sausages by nitrite-degrading Levilactobacillus brevis CHOL1: Combining flavouromics and lipidomics to elucidate the mechanism of aroma formation - Ying Yue; Ning Zhao; Shufeng Yin; Sufang Zhang; Chaofan Ji; Yingxi Chen; Yiwei Dai; Beiwei Zhu; Xinping Lin (Food Chemistry, 2025)

Late Oligocene formation of the Qaidam Basin revealed by calcite U-Pb dating: Insights into the northward growth of Tibetan Plateau - Mengjia Ge; Lei Wu; Shitou Wu; Xuhang Li; Renjie Zhou; Xiubin Lin; Ancheng Xiao; Shufeng Yang; Hanlin Chen (Earth and Planetary Science Letters, 2025)

Performance verification of GNSS/5G tightly coupled fusion positioning in urban occluded environments with a smartphone - Weiwei Song; Haijuan Ding; Laihong Zhang; Liang Chen; Wenfei Guo; Wei Lin; Shufeng Qi (GPS Solutions, 2025)

Metabolomics signature of blood pressure salt sensitivity and its link to cardiovascular disease: A dietary salt-intervention trial - Zhennan Lin; Jianxin Li; Fangchao Liu; Jie Cao; Shufeng Chen; Jichun Chen; Keyong Huang; Yaqin Wang; Hongfan Li; Yan Wang; Jianfeng Huang; Dongfeng Gu; et al. (Science China Life Sciences, 2024)

Elevation-associated pathways mediate aquatic biodiversity at multi-trophic levels along a plateau inland river - Mengru Wei; Tao Feng; Yuqing Lin; Shufeng He; Hanlu Yan; Ruxia Qiao; Qiuwen Chen (Water Research, 2024)

Construction of propolis flavonoids-phospholipid complex loaded O/W submicron emulsion for enhancing in-vivo dilution stability and gastrointestinal absorption efficiency - Liting Yuan; Yan Zhong; Shaobin Lin; Shufeng Chen; Xiaofang Li; Xiaoming Wang; Fengjian Deng; Wanting Wang; Yusheng Li; Linghao Qin (Journal of Food Engineering, 2024)

Boosting oxidative desulfurization from liquid fuels with CuO-MgO assisted by MgMoO4 co-catalyst - Xingye Zeng; Cunhui Lin; Qinggang Ren; Shufeng Shan; Hanlu Wang (Fuel, 2024)

Potential of perennial sorghum for biogas production: Pretreatment with yeast-contained inoculants during anaerobic storage - Xiaolong Tang; Chaosheng Liao; Shufeng Zhou; Cheng Chen; Lin Li; Guangrou Lu; Xiaokang Huang; Mingjie Zhang; Chao Chen; Ping Li (Fuel, 2024)

Antioxidant response to ZnO nanoparticles in juvenile Takifugu obscurus: protective effects of salinity - Yuqing Lin; Jun Wang; Shufeng He; Hanlu Yan; Qiuwen Chen (Ecotoxicology, 2024)

Planktonic/benthic Bathyarchaeota as a “gatekeeper” enhance archaeal nonrandom co-existence and deterministic assembling in the Yangtze River - Shufeng Liu; Yahsuan Lin; Tang Liu; Xuming Xu; Jiawen Wang; Qian Chen; Weiling Sun; Chenyuan Dang; Jinren Ni (Water Research, 2023)

Spatial variation in the community structure and response of benthic macroinvertebrates to multiple environmental factors in mountain rivers - Zaoli Yang; Shufeng He; Tao Feng; Yuqing Lin; Mo Chen; Qinyuan Li; Qiuwen Chen (Journal of Environmental Management, 2023)

Identification of suitable tributaries to compensate fish habitat loss in dammed rivers using environmental DNA metabarcoding - Yuqing Lin; Tao Feng; Lei Tang; Hui Zhang; Jianyun Zhang; Qiuwen Chen; Shufeng He; Ting Li (Hydrobiologia, 2023)

Limits of oxygen isotope palaeoaltimetry in Tibet - Alex Farnsworth; Paul J. Valdes; Lin Ding; Robert A. Spicer; Shi-Hu Li; Tao Su; Shufeng Li; Caitlyn R. Witkowski; Zhongyu Xiong (Earth and Planetary Science Letters, 2023)

Simplification of temperature-programmed oxidation method to characterize petroleum cokes - Cunhui Lin; Chongxian Yan; Xingye Zeng; Shufeng Shan; Yingqiu Zhao; Linhai Duan (Fuel, 2023)

The association of long-term ambient fine particulate matter exposure with blood pressure among Chinese adults - Zhennan Lin; Shufeng Chen; Fangchao Liu; Jianxin Li; Jie Cao; Keyong Huang; Fengchao Liang; Jichun Chen; Hongfan Li; Jianfeng Huang; Dongsheng Hu; Chong Shen; et al. (Environmental Pollution, 2023)

Molecular insights into the circadian clock in marine diatoms - Shufeng Zhang; Yue Wu; Lin Lin; Dazhi Wang (Acta Oceanologica Sinica, 2022)

Quantitative proteomics provides insight into the response of the marine dinoflagellate Prorocentrum donghaiense to changes in ambient phosphorus - Shufeng Zhang; Chunjuan Yuan; Ying Chen; Lin Lin; Dazhi Wang (Journal of Oceanology and Limnology, 2022)

Rap2B knockdown suppresses malignant progression of hepatocellular carcinoma by inactivating the PTEN/PI3K/Akt and ERK1/2 pathways - Linchao Zhu; Ying Sun; Shufeng Zhang; Lin Wang (Molecular and Cellular Biochemistry, 2020)

Major transgression during Late Cretaceous constrained by basin sediments in northern Africa: implication for global rise in sea level - Kaixuan An; Hanlin Chen; Xiubin Lin; Fang Wang; Shufeng Yang; Zhixin Wen; Zhaoming Wang; Guangya Zhang; Xiaoguang Tong (Frontiers of Earth Science, 2017)

Deformation geometry and timing of theWupoer thrust belt in the NE Pamir and its tectonic implications - Xiaogan Cheng; Hanlin Chen; Xiubin Lin; Shufeng Yang; Shenqiang Chen; Fenfen Zhang; Kang Li; Zelin Liu (Frontiers of Earth Science, 2016)

Transcriptional responses of maize seedling root to phosphorus starvation - Hai-Jian Lin; Jian Gao; Zhi-Ming Zhang; Ya-Ou Shen; Hai Lan; Li Liu; Kui Xiang; Maojun Zhao; Shufeng Zhou; Yong-Zhong Zhang; Shi-Bin Gao; Guang-Tang Pan (Molecular Biology Reports, 2013)

Cloning and characterization of miRNAs from maize seedling roots under low phosphorus stress - Zhiming Zhang; Haijian Lin; Yaou Shen; Jian Gao; Kui Xiang; Li Liu; Haiping Ding; Guangsheng Yuan; Hai Lan; Shufeng Zhou; Maojun Zhao; Shibin Gao; et al. (Molecular Biology Reports, 2012)